1979
DOI: 10.1037/0022-3514.37.4.499
|View full text |Cite
|
Sign up to set email alerts
|

Encoding of personal information: Self–other differences.

Abstract: Self-other differences in processing personal information were investigated by having subjects make self-referent (describes you?) or other-referent (describes experimenter?) ratings of personal adjectives. Results from five studies indicated that self-ratings were 'consistently judged as easier to make, and subjects always placed more confidence in these judgments. An analysis of rating •times showed that only adjectives with long rating times were recalled for the unknown-other-referent task (Experiments 2 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

26
257
3
4

Year Published

1980
1980
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 373 publications
(290 citation statements)
references
References 27 publications
26
257
3
4
Order By: Relevance
“…In an effort to solve this problem, researchers compared memory following SR to that following OR (e.g., "Does this word describe your mother?"). Studies usually showed that the SRE was reduced, if not eliminated entirely, when the target referenced in the comparison task was a highly familiar other (e.g., Bower & Gilligan, 1979;Kuiper, 1982;Kuiper & Rogers, 1979)• Further studies suggest other boundary conditions on the SRE. For example, the SRE is shown to be reduced or reversed when imagery tasks are used (Lord, 1980), the semantic comparison task is a desirability rating (Ferguson, Rule, & Carlson, 1983), or the semantic comparison task promotes organization (but the SR task does not; Klein & Kihlstrom, 1986)• Despite these null findings and reversals, our narrative inspection of the literature suggests that the SRE appears more often than not.…”
Section: Historical Overview Of Sre Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…In an effort to solve this problem, researchers compared memory following SR to that following OR (e.g., "Does this word describe your mother?"). Studies usually showed that the SRE was reduced, if not eliminated entirely, when the target referenced in the comparison task was a highly familiar other (e.g., Bower & Gilligan, 1979;Kuiper, 1982;Kuiper & Rogers, 1979)• Further studies suggest other boundary conditions on the SRE. For example, the SRE is shown to be reduced or reversed when imagery tasks are used (Lord, 1980), the semantic comparison task is a desirability rating (Ferguson, Rule, & Carlson, 1983), or the semantic comparison task promotes organization (but the SR task does not; Klein & Kihlstrom, 1986)• Despite these null findings and reversals, our narrative inspection of the literature suggests that the SRE appears more often than not.…”
Section: Historical Overview Of Sre Researchmentioning
confidence: 99%
“…We expect results for these dimensions to provide important clues regarding the basis of the SRE. Thus, for example, if the use of a distractor task has no impact on the SRE for semantic-SR comparisons but increases the SRE for SR-OR comparisons, then it may be that OR tasks benefit more from rehearsal strategies, as some reseachers have argued (Kuiper & Rogers, 1979).…”
Section: Exploratory Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…(p. 189) Although it is easy to demonstrate the autobiographical character of memory to ourselves by means of such personal retrievals, empirical confirmation of the importance of self-reference in perception and memory is only a very recent development. Rogers, Kuiper, and Kirker ( 1977) provided the first of several demonstrations that information is especially well remembered if the person considers the relation of information to self at the time of initial experience (see also , Bower & Gilligan, 1979;Kuiper & Rogers, 1979;Lord, 1980). Brenner (1973Brenner ( , 1976 found that in a group setting, subjects focused on their own performance a t the expense of retaining information from the just preceding or just following performances of others.…”
Section: Organization Of Memory I N Relation To Selfmentioning
confidence: 99%
“…These results converge to show that both world views as a distal force and self-views as a proximal force matter in people's subjective evaluation of their lives. The Why and How.As a cognitive framework that helps people organize information about the self and guide their social behavior, the utility of positive and negative self-views has received growing attention in the past three decades (e.g., Kuiper & Rogers, 1979;Markus, 1977). Theory and research have demonstrated that self-views function like schemas and beliefs to affect psychological outcomes, fueling the popularity of self-help books and programs designed to boost self-esteem (Swann & Seyle, 2005).…”
mentioning
confidence: 99%